The Mother Narrative Transformed: Criminalizing the Immigrant Mother in Jordi Sierra i Fabra’s “Barrios altos” - Diana Aramburu (Studies in 20th & 21st Century Literature, 2019)
With the ongoing financial crisis and the influx of refugees and other migrant communities in Spain, the "immigrant problem," combined with a narrative that reflects upon the economic crisis, has become a focal point for numerous genres, including that of crime fiction. While the immigrant narrative has been mostly presented from the vantage point of the autochthonous community, recent contributions to migrant literature in Spain have refocalized this perspective, and privilege the immigrant’s plight to evoke the reader’s empathy. This article examines how Jordi Sierra i Fabra’s 2013 “Barrios altos” (“A High-End Neighborhood,” 2011) problematizes the representation of the immigrant mother in contemporary Spanish crime literature. By exploring how and why the Filipino maid, Felipa, is criminalized in Sierra i Fabra's short story, this article argues that Sierra i Fabra combines a narrative of criminalization with a revenge narrative to complicate our reading of the immigrant mother, a character that cannot be read as a criminal unless she is understood as a victim as well. The immigrant mother’s hybrid condition in Sierra i Fabra’s short story signifies a transformation of the mother in crime fiction by presenting a character type that transgresses the border between victimhood and criminality due to a heightening in her maternal vulnerability.
Keywords: immigrant mothers in crime fiction; Jordi Sierra i Fabra; & quot; Barrios altos& quot; & quot; A High-End Neighborhood& quot; criminal mothers; criminal mother narrative